The Influence of Emotional Intelligence and Student Learning Behavior Through Student Motivation on Student Learning Outcomes - Rauf, Abdul; Suarman, Suarman; Kartikowati, Sri (Journal of Educational Sciences, 2020)
Learning outcomes are a description on how students understand the material presented by the teacher. Learning outcomes are output values ​​in the form of numbers or letters obtained by students after receiving learning material through a test or exam delivered by the teacher. This study aims to determine the effect of emotional intelligence, learning behavior, motivation on learning outcomes either simultaneously or partially. The method used in this research is descriptive method. Based on the data analysis and hypothesis testing that has been carried out in this study, the results of the research show that there is an influence of Emotional Intelligence and Learning Behavior on Motivation with a t-count of 5,912 emotional intelligence on motivation and learning behavior with a bear t count of 4.408 thus it can It is known that emotional intelligence and learning behavior affect learning motivation. The conclusions are as follows: 1) The influence of Emotional Intelligence and Learning Behavior on Motivation. 2) The influence of Emotional Intelligence and Learning Behavior, Motivation on student learning outcomes.